District mental healthcare plans for five low-and middle-income countries: Commonalities, variations and evidence gaps. (January 2016) - Hanlon, Charlotte; Fekadu, Abebaw; Jordans, Mark; Kigozi, Fred; Petersen, Inge; Shidhaye, Rahul; Honikman, Simone; Lund, Crick; Prince, Martin; Raja, Shoba; Thornicroft, Graham; Tomlinson, Mark; et al.
Abstract : Background: Little is known about the service and system interventions required for successful integration of mental healthcare into primary care across diverse low- and middle-income countries (LMIC). Aims: To examine the commonalities, variations and evidence gaps in district-level mental healthcare plans (MHCPs) developed in Ethiopia, India, Nepal, Uganda and South Africa for the PRogramme for Improving Mental health carE (PRIME). Method: A comparative analysis of MHCP components and human resource requirements. Results: A core set of MHCP goals was seen across all countries. The MHCPs components to achieve those goals varied, with most similarity in countries within the same resource bracket (low income v. middle income). Human resources for advanced psychosocial interventions were only available in the existing health service in the best-resourced PRIME country. Conclusions: Application of a standardised methodological approach to MHCP across five LMIC allowed identification of core and site-specific interventions needed for implementation.